Regularização fundiária urbana com participação popular experiência e enfrentamentos no município de Taboão da Serra - Dias, João Marcus Pires (2012)
This thesis aims to develop a case study on the process of regularization with participation in a subdivision located in the Municipality of Taboão da Serra, São Paulo metropolitan region. The main objective of this study is to see what were the intricacies of the power circuit in which this form of participatory management was present and how were their clashes and confrontations. Are inserted into this circuit to municipal public administration represented by the Municipal Housing and Urban Development, the instances of popular representation within the field of activity in the regulation of subdivision and local actors. Popular participation is set to direct mechanisms of representation, combining the concepts of participatory and deliberative democracy, aiming to expand the traditional spheres of political decisions, typical of representative democracy. The main hypothesis to be achieved by this study is to detect conditions which, in the process of regularization of the settlement were implemented to make it happen for deliberation and social control of public administration. To develop this study were considered as methodological resources contributions and theoretical reflections, documentary and bibliographic survey, field research, secondary data analysis and interviews with key actors involved in the process of regularization of the area in question